Questionnaires to Examine Back Pain Beliefs Held by Health Care Professionals - Chen, G.; Tan, Boon; Jia, H.; O'Sullivan, Peter; Burnett, A. (Lippincott, Williams and Wilkins, 2011)
Study Design. Observational cross-sectional study. Objective. To perform a psychometric evaluation of Simplified Chinese versions of back pain beliefs questionnaires for use in health care professionals living in mainland China. Summary of Background Data. Back pain beliefs are of importance in the development of chronic low back pain (LBP) and disability. Different types of beliefs exist with regard to LBP and these include inevitable consequences of LBP and fear-avoidance beliefs.LBP beliefs held by health care providers are also known to influence their patients’ pain beliefs and can contribute to the development of chronic LBP and disability. At present, validated questionnaires such as the Back Beliefs Questionnaire, Health Care Providers’ Pain and Impairment Relationship Scale, and Fear-Avoidance Beliefs Questionnaire are commonly used to investigate back pain beliefs held by health care professionals working in western countries. There are no published nor validated Simplified Chinese versions to allow investigation of back pain beliefs in health care professionals living in mainland China. Methods. The English versions of the earlier mentioned questionnaires were translated and culturally adapted into Simplified Chinese using the double-back-translation method. A psychometric evaluation of the translated questionnaires was conducted on 65 health care professionals (rehabilitation medicine specialists, osteopaths, and nurses), with and without LBP, practicing in Shanghai, China. The questionnaires were completed twice within 7- to 10-day period.Results. The Back Beliefs Questionnaire, Health Care Providers’ Pain and Impairment Relationship Scale, and Fear-Avoidance Beliefs Questionnaire (work and physical subscales) had acceptable internal consistency (Cronbach α range: 0.70–0.87) and construct validity ( r = 0.40–0.49, P < 0.05), good reproducibility (Intraclass correlation coefficients, ICC (2,1) range: 0.85–0.93) and an absence of any floor or ceiling effects. Conclusion. This study showed that the Simplified Chinese versions of back pain beliefs questionnaires are valid and reliable. Therefore, these questionnaires can be used in research involving Chinese health care professionals living in mainland China.